20(S)‐ginsenoside‐Rg3 reverses temozolomide resistance and restrains epithelial‐mesenchymal transition progression in glioblastoma. Issue 1 (14th December 2018) - Chen, Zheng; Wei, Xiangyu; Shen, Lin; Zhu, Hanshuo; Zheng, Xuesheng
Abstract : Glioblastoma multiforme (GBM) is one of the most malignant human intracranial tumors. Temozolomide (TMZ) is the primary alkylating agent for GBM patients. However, many GBM patients are resistant to TMZ. Therefore, patients with GBM urgently need more effective therapeutic options. 20(S)‐ginsenoside‐Rg3 (20(S)‐Rg3) is a natural chemical with anti‐tumor effects, but at present there is little understanding of its functional mechanism. Several research reports have demonstrated that O 6 ‐methylguanine DNA‐methyltransferase (MGMT) repairs damaged DNA and contributes to TMZ resistance in gliomas. In addition, recent studies have shown that MGMT gene expression could be regulated by the Wnt/β‐catenin pathway. However, whether 20(S)‐Rg3 inhibits MGMT expression and augments chemosensitivity to Temozolomide (TMZ) in glioma cells remains unclear. In this study, we explored the modulating effects of 20(S)‐Rg3 on MGMT. We used glioma cell lines, primary cell strain (including T98G, U118 and GBM‐XX; all of them are MGMT‐positive glioma cell lines) and xenograft glioma models to examine whether 20(S)‐Rg3 increased the sensitivity to TMZ and to reveal the underlying mechanisms. We found that the MGMT expression was effectively downregulated by 20(S)‐Rg3 via the Wnt/β‐catenin pathway in glioma cell lines, and TMZ resistance was significantly reversed by 20(S)‐Rg3. Meanwhile, 20(S)‐Rg3 shows no obvious cytotoxicity at its effective dose and is well tolerated in vivo. In addition, we found that 20(S)‐Rg3 significantly restrains the epithelial‐mesenchymal transition (EMT) progression of glioma cells. Taken together, these results indicate that 20(S)‐Rg3 may be a novel agent to use in treatment of GBM, especially in TMZ‐resistant GBM with high MGMT expression. Abstract : In this study, we demonstrated, for the first time to the best of our knowledge, that 20(S)‐Rg3 potentiates chemosensitivity to TMZ in MGMT‐positive glioma cells by modulating Wnt/β‐catenin/MGMT pathways. We revealed that 20(S)‐Rg3 effectively restrains the epithelial‐mesenchymal transition progression of glioma cells.